Age‐ratio bias among hunter‐based surveys of Eurasian Wigeon Anas penelope based on wing vs. field samples. (26th December 2014) - Fox, Anthony D.; Clausen, Kevin Kuhlmann; Dalby, Lars; Christensen, Thomas Kjær; Sunde, Peter
Abstract : We compared age and sex ratios among Eurasian Wigeon Anas penelope derived from Danish field observations and hunter‐based shot samples throughout an entire winter. Sex ratios did not differ significantly between the two samples. Overall, first‐year males were more than three times more likely to be represented than adult males in the hunter sample compared with field samples and were 7–20 times overrepresented in the hunting sample at the beginning of the season. These results confirm the need to account for such bias and its temporal variation when using the results of hunting surveys to model population parameters. Hunter‐shot age ratios may provide a long‐term measure of reproductive success of dabbling duck flyway populations given an understanding of such bias.